Paracaspase MALT1 regulates glioma cell survival by controlling endo‐lysosome homeostasis - Jacobs, Kathryn A; André‐Grégoire, Gwennan; Maghe, Clément; Thys, An; Li, Ying; Harford‐Wright, Elizabeth; Trillet, Kilian; Douanne, Tiphaine; Alves Nicolau, Carolina; Frénel, Jean‐Sébastien; Bidère, Nicolas; Gavard, Julie (The EMBO journal, 2020)
Glioblastoma is one of the most lethal forms of adult cancer with a median survival of around 15 months. A potential treatment strategy involves targeting glioblastoma stem‐like cells (GSC), which constitute a cell autonomous reservoir of aberrant cells able to initiate, maintain, and repopulate the tumor mass. Here, we report that the expression of the paracaspase mucosa‐associated lymphoid tissue l (MALT1), a protease previously linked to antigen receptor‐mediated NF‐κB activation and B‐cell lymphoma survival, inversely correlates with patient probability of survival. The knockdown of MALT1 largely impaired the expansion of patient‐derived stem‐like cells in vitro , and this could be recapitulated with pharmacological inhibitors, in vitro and in vivo . Blocking MALT1 protease activity increases the endo‐lysosome abundance, impairs autophagic flux, and culminates in lysosomal‐mediated cell death, concomitantly with mTOR inactivation and dispersion from endo‐lysosomes. These findings place MALT1 as a new druggable target involved in glioblastoma and unveil ways to modulate the homeostasis of endo‐lysosomes. Synopsis This study unveils that the paracaspase activity of MALT1, which was previously linked to antigen receptor‐mediated NF‐κB activation and lymphomas, is decisive for the expansion of glioblastoma stem‐like cells (GSC), highlighting potential therapeutic strategies against brain cancers. Expression and catalytic activity of MALT1 are required for GSC expansion. Pharmacological targeting of MALT1 is lethal to GSCs and reduces the expansion of established tumors in mice. MALT1 depletion results in an increased endo‐lysosomal compartment and decreased mTOR signaling. MALT1 expression negatively correlates to that of RNA‐binding protein Quaking to control endo‐lysosomal biogenesis. Graphical Abstract Protease MALT1 impairs lysosome biogenesis and increases mTOR signalling and autophagic flux in glioma stem cells.